Recycled concrete aggregate specimen preparation method, test device and test method

By adding epoxy resin to the bottom of the regenerative concrete aggregate and for stretching and destruction testing, it is difficult to quantitatively evaluate the adhesion of the regenerative concrete interface in existing technology, and the accurate determination of its interface bonding power is realized. Provide technology guarantee for its promotion.

CN118706557BActive Publication Date: 2025-01-28ZHEJIANG TIANZAO ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411177605.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-08-20
Filing Date
2024-08-26
Publication Date
2025-01-28
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

It is difficult to quantitatively evaluate the interfacial bonding force mechanical properties of recycled concrete aggregates due to brittle damage.

Method used

By adding epoxy resin to the bottom of the aggregate, prepare regenerative concrete aggregate test parts, and use stretching and destructive test to determine the adhesion of its interface.

Benefits of technology

The quantitative testing and evaluation of the regenerative concrete interface interface is realized, and technical guarantees are provided to promote the promotion and sustainable application of technical guarantees.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118706557B_ABST
    Figure CN118706557B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a recycled concrete aggregate specimen, a testing device and a testing method. The method for preparing a recycled concrete aggregate specimen comprises the following steps: screening recycled aggregates with a particle size deviation less than or equal to a set particle size deviation as the aggregate to be tested; placing the aggregate to be tested in a lower forming mold, and controlling the gap between the aggregates to be tested to be less than the set gap; pouring epoxy resin into the lower forming mold until the epoxy resin is filled to a set height, so as to obtain an epoxy resin layer formed at the lower part of the aggregate to be tested after standing and hardening; pouring cement mortar into an upper forming mold, and vibrating and forming, so as to obtain a cement mortar layer formed at the upper part of the aggregate to be tested after standing and hardening; and curing to a set age under standard test conditions to obtain a recycled concrete aggregate specimen. The recycled concrete aggregate specimen can be used to determine the interfacial bonding force of recycled concrete aggregates, providing technical guarantee for the promotion and sustainable application of recycled concrete aggregates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of civil engineering tests, and in particular to a recycled concrete aggregate specimen preparation method, a testing device and a testing method. Background Art

[0002] Compared with natural aggregates, the surface of recycled concrete aggregates is often covered with a layer of mortar, which makes the internal aggregate-paste structure of recycled concrete more complex. Usually, the interface porosity of new mortar or old mortar inside recycled concrete is high, which absorbs water during the mixing process and causes the enrichment and orientation of CH crystals during the hydration process, thus becoming the weakest link of recycled concrete, resulting in more serious durability problems of recycled concrete. In addition, the interfacial adhesion of recycled aggregates is very complex. Factors such as different aggregate types, water-cement ratio of fresh mortar, slump and curing temperature all affect the interfacial adhesion of aggregates. Therefore, it is necessary to quantitatively test the interfacial adhesion between recycled concrete aggregates and fresh mortar.

[0003] There are some methods and devices for quantitatively testing the adhesion between asphalt or asphalt film and aggregate in the existing technology. However, asphalt, as a tough organic material, is significantly different from concrete. Concrete is very prone to brittle failure under tensile load due to the presence of more pores inside and higher elastic modulus. It is difficult to quantitatively evaluate the mechanical properties of the aggregate interface. Summary of the invention

[0004] Based on this, it is necessary to provide a recycled concrete aggregate specimen preparation method, a testing device and a testing method to address the problem that the existing recycled concrete is prone to brittle failure and it is difficult to quantitatively evaluate the mechanical properties of the aggregate interface.

[0005] A method for preparing a recycled concrete aggregate specimen comprises the following steps:

[0006] Screen the recycled aggregates whose particle size deviation is less than or equal to the set particle size deviation as the aggregate to be tested;

[0007] The aggregate to be tested is placed in the lower forming die, and the gap between the aggregates to be tested is controlled to be smaller than the set gap;

[0008] Pour epoxy resin into the lower forming mold until the epoxy resin is filled to a set height, so as to obtain an epoxy resin layer formed at the bottom of the aggregate to be tested after standing and hardening;

[0009] Pour cement mortar into an upper forming mold and vibrate to form a cement mortar layer formed on the upper part of the aggregate to be tested after standing and solidifying; and

[0010] Under standard test conditions, the recycled concrete aggregate specimens are cured to the set age.

[0011] In one of the embodiments, in the step of screening recycled aggregates with a particle size deviation less than or equal to a set particle size deviation as aggregate to be tested, the set particle size deviation is 3 mm.

[0012] In one of the embodiments, in the step of placing the aggregate to be tested in the lower forming mold and controlling the gap between the aggregate to be tested to be smaller than the set gap, the set gap is 2 mm.

[0013] In one of the embodiments, in the step of screening recycled aggregates with a particle size deviation less than or equal to a set particle size deviation as the aggregate to be tested, the particle size of the recycled aggregate ranges from 5 mm to 31.5 mm, and the sphericity of the recycled aggregate is greater than or equal to 0.9.

[0014] In one embodiment, in the step of pouring epoxy resin into the lower molding die until the epoxy resin is filled to a set height to obtain an epoxy resin layer formed at the bottom of the aggregate to be tested after standing and hardening, the set height is equal to half the height of the aggregate to be tested.

[0015] In one of the embodiments, in the recycled concrete aggregate specimen preparation method, the outer diameter of the upper forming mold is smaller than the outer diameter of the lower forming mold.

[0016] In one of the embodiments, in the recycled concrete aggregate specimen preparation method, the upper forming mold is made of Teflon material.

[0017] A testing device, comprising:

[0018] A specimen fixture, the specimen fixture comprising a lower fixing component and an upper transition component, the lower fixing component is used to fix the epoxy resin of the recycled concrete aggregate specimen, and the upper transition component is used to bond to the cement mortar of the recycled concrete aggregate specimen;

[0019] A stretching fixture, the stretching fixture comprising a lower stretching component connected to the lower fixing component and an upper stretching component connected to the upper transition component;

[0020] A power device, the power device is connected to the upper stretching member and the lower stretching member respectively to drive the upper stretching member to move up and down;

[0021] A load sensor, wherein the load sensor is disposed on the upper adapter component to collect the ultimate load when the recycled concrete aggregate specimen is destroyed; and

[0022] A data acquisition device is electrically connected to the load sensor to record the ultimate load when the recycled concrete aggregate specimen is destroyed.

[0023] A testing method comprises the steps of:

[0024] bonding the recycled concrete aggregate specimen to the upper transition component;

[0025] Clamping a lower fixing member to a lower tensile member, and placing the recycled concrete aggregate specimen into the lower fixing member;

[0026] clamping the upper adapter member to the upper stretching member;

[0027] Starting the power device to drive the upper stretching component to drive the upper transfer component to stretch the recycled concrete aggregate specimen;

[0028] By means of a load sensor and a data acquisition device, sampling the tensile failure load of the recycled concrete aggregate specimen until the recycled concrete aggregate specimen is destroyed; and

[0029] The interfacial bonding force of the recycled concrete aggregate specimen is calculated according to the ultimate load when the recycled concrete aggregate specimen is destroyed.

[0030] In one embodiment, the step of bonding the recycled concrete aggregate specimen to the upper transition component comprises the steps of:

[0031] The recycled concrete aggregate specimen is taken out of the mold and dried in an oven;

[0032] Applying adhesive to the upper surface of the recycled concrete aggregate specimen;

[0033] placing the upper adapter component on the adhesive; and

[0034] The adhesive around the upper transition component is removed and maintenance is performed.

[0035] In one embodiment, the ultimate load when the recycled concrete aggregate specimen is destroyed is within the range of 20% to 80% of the measuring range of the power device, the accuracy of the power device is 1%, and the minimum indication of the power device is 1N.

[0036] In one of the embodiments, in the step of sampling the tensile failure load of the recycled concrete aggregate specimen by means of a load sensor and a data acquisition device until the recycled concrete aggregate specimen is destroyed, the sampling frequency of the load sensor is greater than or equal to 10 Hz.

[0037] In one of the embodiments, in the step of starting the power device to drive the upper tensile component to drive the upper adapter component to stretch the recycled concrete aggregate specimen, the tensile loading speed of the power device is controlled within the range of 0.1 mm / min to 1 mm / min.

[0038] The present application adds epoxy resin to the bottom of the aggregate to make a recycled concrete aggregate specimen, and then measures the interfacial bonding force of the recycled concrete aggregate through a tensile failure test, thereby being able to quantitatively evaluate the effect of the surface-attached mortar layer of the recycled concrete aggregate on the bonding performance of the aggregate interface, providing technical support for the promotion and sustainable application of recycled concrete aggregate. The recycled aggregate specimen preparation method provided by the present application is easy to prepare, the installation of the test device is simple and quick, the test method is accurate, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 A schematic diagram of the steps of a method for preparing a recycled concrete aggregate specimen provided in one embodiment of the present application;

[0040] Figure 2 A schematic cross-sectional view of a recycled concrete aggregate specimen prepared by the recycled concrete aggregate specimen preparation method according to the above embodiment of the present application is shown;

[0041] Figure 3 A schematic diagram of the structure of a testing device provided for one embodiment of the present application;

[0042] Figure 4 A schematic diagram of the steps of a testing method provided for one embodiment of the present application;

[0043] Figure 5 A schematic diagram of step S100 of the testing method according to the above embodiment of the present application is shown.

[0044] Figure numerals: 11, aggregate to be tested; 12, epoxy resin layer; 13, cement mortar layer; 21, lower fixing component; 22, upper transfer component; 23, lower tensile component; 24, upper tensile component; 25, power device; 26, load sensor; 27, data acquisition device. DETAILED DESCRIPTION

[0045] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0046] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.

[0047] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0048] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0049] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0050] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "upper", "lower", "left", "right" and similar expressions used herein are for illustrative purposes only and are not intended to be the only implementation method.

[0051] Based on the problem that the existing recycled concrete is prone to brittle failure and it is difficult to quantitatively evaluate the mechanical properties of the aggregate interface, the present application provides a recycled concrete aggregate specimen preparation method, a test device and a test method. The present application adds epoxy resin to the bottom of the aggregate to make a recycled concrete aggregate specimen, and then measures the interfacial bonding force of the recycled concrete aggregate through a tensile failure test, so as to quantitatively evaluate the influence of the surface attached mortar layer of the recycled concrete aggregate on the bonding performance of the aggregate interface.

[0052] Specifically, Figure 1 As shown, the present application provides a method for preparing a recycled concrete aggregate specimen, comprising the steps of:

[0053] S100, screening recycled aggregates with a particle size deviation less than or equal to a set particle size deviation as aggregates to be tested;

[0054] S200, placing the aggregate to be tested in the lower forming mold, and controlling the gap between the aggregates to be tested to be smaller than the set gap;

[0055] S300, pouring epoxy resin into the lower molding die until the epoxy resin is filled to a set height, so as to obtain an epoxy resin layer formed at the bottom of the aggregate to be tested after standing and hardening;

[0056] S400, placing an upper molding die above the epoxy resin layer so that the upper molding die wraps the upper part of the aggregate to be tested;

[0057] S500, pouring cement mortar into an upper forming mold and vibrating the mold to obtain a cement mortar layer formed on the upper part of the aggregate to be tested after standing and solidifying; and

[0058] S600. Under standard test conditions, the recycled concrete aggregate specimens are cured to the set age to obtain.

[0059] It can be understood that, through step S100, the recycled aggregate is screened so that the particle size deviation of the aggregate to be tested is similar, which is convenient for calculating the interfacial bonding force of the recycled concrete aggregate specimen, through step S200, the aggregate to be tested is laid in the lower molding mold, and the gap between the aggregates to be tested is controlled to simulate the gap between the recycled aggregates in actual use, through step S300, epoxy resin is poured to the bottom of the aggregate to be tested, and the aggregate to be tested is fixed by epoxy resin material, through steps S400 and S500, cement mortar is poured to the top of the aggregate to be tested, and the bubbles in the cement mortar and the aggregate to be tested are discharged by vibration, and the cement mortar fills the gap between the aggregates to be tested, so that the cement mortar is in full contact with the aggregate to be tested, and is left to solidify and harden to form, and through step S600, under standard test conditions, it is cured to a set age, thereby obtaining a recycled concrete aggregate specimen. Among them, the standard test conditions are environmental conditions of temperature 20°C and humidity greater than 95%, and the set age is at least 28 days.

[0060] like Figure 2 The figure shows a recycled concrete aggregate specimen prepared according to the recycled concrete aggregate specimen preparation method of the present application. The lower part of the aggregate to be tested 11 is an epoxy resin layer 12 , and the upper part of the aggregate to be tested 11 is a cement mortar layer 13 .

[0061] The recycled concrete aggregate specimen uses epoxy resin material to fix the aggregate to be tested by pouring an epoxy resin layer at the bottom of the aggregate to be tested, thereby avoiding brittle failure of the recycled concrete aggregate due to tensile load during tensile testing.

[0062] For example, in one of the embodiments, in step S100, recycled aggregates with a particle size deviation less than or equal to a set particle size deviation are screened as aggregates to be tested, and the set particle size deviation is less than or equal to 3 mm.

[0063] For example, in one of the embodiments, in step S200, placing the aggregate to be tested in the lower forming mold, and controlling the gap between the aggregates to be tested to be smaller than the set gap, the set gap is 2 mm.

[0064] For example, in one embodiment, the particle size of the recycled aggregate ranges from 5 mm to 31.5 mm, and the sphericity of the recycled aggregate is greater than or equal to 0.9. By controlling the particle size and sphericity of the recycled aggregate, the aggregate to be tested is made closer to a sphere, which facilitates subsequent testing and calculation of the interfacial bonding force of the recycled concrete aggregate specimen.

[0065] Preferably, in one embodiment, in step S300, epoxy resin is poured into the lower molding die until the epoxy resin is filled to a set height, so as to obtain an epoxy resin layer formed at the lower part of the aggregate to be tested after standing and hardening, and the set height is equal to half the height of the aggregate to be tested. Such a setting enables the epoxy resin to wrap more of the aggregate to be tested, so that it can be more tightly combined with the aggregate to be tested, and can better protect the aggregate to be tested in the tensile failure test.

[0066] Preferably, in one of the embodiments, in the recycled concrete aggregate specimen preparation method, the outer diameter of the upper molding mold is smaller than the outer diameter of the lower molding mold, so that the outer diameter of the cement mortar layer is smaller than the outer diameter of the epoxy resin layer, thereby forming a step structure to facilitate clamping and fixing the epoxy resin layer.

[0067] For example, in one embodiment, the dimensions of the lower molding die are 100 mm in length, 100 mm in width, and 30 mm in height, and the dimensions of the upper molding die are 70 mm in length, 70 mm in width, and 25 mm in height.

[0068] Preferably, since cement mortar and epoxy resin are easily adhered to the forming mold during the process of coagulation and hardening, in one embodiment, the upper forming mold is made of Teflon material. Teflon material is a non-stick material, and the upper forming mold and the lower forming mold made of Teflon material can be quickly demolded, and a more complete recycled concrete aggregate specimen can be obtained.

[0069] It is worth noting that the upper forming mold can also be made of other materials, but it needs to be coated with oil or other release agents that facilitate demoulding before use so that the manufactured recycled concrete aggregate specimen can be removed.

[0070] Furthermore, if Figure 3As shown, the present application provides a testing device for testing the recycled concrete aggregate specimen prepared according to the above-mentioned recycled concrete aggregate specimen preparation method, and the testing device may include a specimen fixture, a tensile fixture, a power device 25, a load sensor 26 and a data acquisition device 27. The specimen fixture may include a lower fixing component 21 and an upper transition component 22, wherein the lower fixing component 21 is used to fix the epoxy resin of the recycled concrete aggregate specimen, and the upper transition component 22 is used to bond to the cement mortar of the recycled concrete aggregate specimen. The tensile fixture includes a lower tensile component 23 and an upper transition component 22, wherein the lower tensile component 23 is used to connect the lower fixing component 21, and the upper tensile component 24 is used to connect the upper transition component 22. The power device 25 is respectively connected to the upper tensile component 24 and the lower tensile component 23 to drive the upper tensile component 24 and / or the lower tensile component 23 to move up and down. The load sensor 26 is disposed on the upper adapter component 22 to collect the ultimate load when the recycled concrete aggregate specimen is destroyed. The data acquisition device 27 is electrically connected to the load sensor 26 to record the ultimate load when the recycled concrete aggregate specimen is destroyed.

[0071] More specifically, the upper transition component 22 includes a bonding platform and an upper pull rod, the bonding platform is used to bond the cement mortar bonding platform of the recycled concrete aggregate specimen, and the free end of the upper pull rod has a thread, which can be fixedly connected to the upper tensile component 24 through the thread. The power device 25 can be a hydraulic servo test machine, which can achieve tensile loading at a constant speed.

[0072] Furthermore, if Figure 4 As shown, the present application also provides a test method for testing a recycled concrete aggregate specimen prepared according to the above-mentioned recycled concrete aggregate specimen preparation method, and the test method comprises the steps of:

[0073] S710, bonding the recycled concrete aggregate specimen to the upper transition component;

[0074] S720, clamping the lower fixing component to the lower tensile component, and loading the recycled concrete aggregate specimen into the lower fixing component;

[0075] S730, clamping the upper adapter component to the upper stretching component;

[0076] S740, starting the power device to drive the upper stretching component to drive the upper transfer component to stretch the recycled concrete aggregate specimen;

[0077] S750, sampling the tensile failure load of the recycled concrete aggregate specimen through a load sensor and a data acquisition device until the recycled concrete aggregate specimen is destroyed; and

[0078] S760. Calculate the interfacial bonding force of the recycled concrete aggregate specimen according to the ultimate load when the recycled concrete aggregate specimen is destroyed.

[0079] It can be understood that the recycled concrete aggregate specimen is assembled to the power device through steps S710, S720 and S730, the recycled concrete aggregate specimen is subjected to a tensile failure test through steps S740 and S750, and the test data is recorded, and the interfacial bonding force of the recycled concrete aggregate specimen is calculated through step S760.

[0080] The calculation formula of the interfacial bonding force of the recycled concrete aggregate specimen is: σ=F / A; where σ is the interfacial bonding force between the aggregate to be tested and the cement mortar of the recycled concrete aggregate specimen, F is the tensile failure load measured by the load sensor, and A is the horizontal force-bearing area of ​​the recycled concrete aggregate specimen. The interfacial bonding force of the recycled concrete aggregate specimen can be calculated according to this calculation formula.

[0081] Preferably, the test method provided in the present application can more accurately calculate the interfacial bonding strength of recycled concrete by obtaining the average tensile failure stress through multiple tests, wherein the number of tests is at least 6 times.

[0082] Furthermore, if Figure 5 As shown, in one embodiment, the step of bonding the recycled concrete aggregate specimen to the upper transition component comprises the steps of:

[0083] S711, taking the recycled concrete aggregate specimen out of the mold and drying it in an oven;

[0084] S712, applying an adhesive to the upper surface of the recycled concrete aggregate specimen;

[0085] S713, placing the upper transfer component on the adhesive; and

[0086] S714, remove the adhesive around the upper transfer component and perform maintenance.

[0087] It can be understood that, through step S711, the water vapor in the recycled concrete aggregate specimen is removed to keep the recycled concrete aggregate specimen dry, through steps S712 and S713, the upper transition component is bonded to the upper surface of the recycled concrete aggregate specimen, and through step S714, the upper transition component and the recycled concrete aggregate specimen are bonded more firmly.

[0088] Optionally, in one of the embodiments, in step S711, the recycled concrete aggregate specimen is taken out from the mold and dried in an oven at 105° C. for at least 24 hours to fully dry the recycled concrete aggregate specimen.

[0089] Optionally, in one embodiment, the ultimate load when the recycled concrete aggregate specimen is destroyed is within the range of 20% to 80% of the measuring range of the power device, the accuracy of the power device is 1%, and the minimum indication of the power device is 1 N. In this way, the interfacial bonding force of the recycled concrete aggregate specimen can be tested and calculated more accurately by selecting a suitable measuring range.

[0090] Preferably, in the tensile failure test, it is difficult to accurately capture the moment of failure of the recycled concrete aggregate specimen, therefore, in one embodiment, in the step of sampling the tensile failure load of the recycled concrete aggregate specimen through the load sensor and the data acquisition device until the recycled concrete aggregate specimen is destroyed, the sampling frequency of the load sensor is greater than or equal to 10 Hz. In this way, the load of the recycled concrete aggregate specimen at the moment of failure can be more accurately collected to more accurately calculate the interfacial bonding force of the recycled concrete aggregate specimen.

[0091] In the tensile failure test, the faster the stretching speed, the higher the load applied to the specimen, which makes it difficult to collect the load at the moment the specimen is destroyed. The slower the stretching speed, the lower the load applied to the specimen, which causes the test time to be too long and it is easy to collect too much useless data. Therefore, the stretching speed should not be too fast or too small.

[0092] Preferably, in one embodiment, in the step of starting the power device and driving the upper stretching component to drive the upper adapter component to stretch the recycled concrete aggregate specimen, the tensile loading speed of the power device is controlled within the range of 0.1 mm / min to 1 mm / min. In this way, it can ensure that the load on the specimen at the moment of destruction can be accurately collected, and it can avoid collecting too much useless test data.

[0093] It is worth noting that the adhesive is a high-strength structural adhesive, and the interfacial bonding force of the adhesive is greater than the interfacial bonding force of the recycled concrete aggregate. When the adhesive is damaged, the measured test data is invalid.

[0094] In summary, this application realizes the quantitative test and evaluation of the interfacial bonding force between concrete and fresh cement mortar, and provides technical guarantee for the promotion and sustainable application of recycled concrete aggregate. The recycled aggregate specimen preparation method provided in this application is convenient to prepare, the installation of the test device is simple and fast, the test method is accurate, and it has broad application prospects.

[0095] According to the above test method, the present application provides an example of a specific tensile failure test.

[0096] Cement mortar and recycled concrete aggregate were selected according to Table 1 below, and 8 specimens were prepared for each group of mortar and aggregate according to the above-mentioned recycled concrete aggregate specimen preparation method.

[0097] Specifically, the particle size deviation of the selected recycled aggregate does not exceed 3mm. The selected aggregate is placed tightly in the lower molding die, the gap between the aggregates is controlled to be less than 2mm, and then the epoxy resin is slowly poured into the mold from the edge of the lower molding die, and the epoxy resin is filled to half the height of the aggregate. After the epoxy resin hardens into an epoxy resin layer, an upper molding die with an internal size of 25mm×70mm×70mm and a material of Teflon is placed on the upper part of the center of the specimen, and then cement mortar is poured into the upper molding die and vibrated for 10 seconds to form and smooth the mortar surface.

[0098] Table 1 Water-binder ratio of cement mortar, mortar strength and particle size of recycled aggregate

[0099]

[0100] The prepared specimens were demoulded 24 hours after molding and cured for 28 days under standard test conditions. Before testing, the specimens were taken out and dried in an oven at 105°C for 24 hours.

[0101] Apply adhesive to the upper surface of the dried specimen and place the upper transition component on the adhesive in the correct position, remove the adhesive overflowing around it and continue curing for 24 hours.

[0102] After the curing is completed, the lower fixing component is fixedly connected to the lower tensile component, and the specimen is placed in the lower fixing component. The upper adapter component is fixedly connected to the upper tensile component, and the upper tensile component is driven by a power device. The load sensor is connected to an external data acquisition device. Load is applied at a speed of (0.5±0.1) mm / min until the specimen is destroyed. The interface adhesion is calculated based on the limit load obtained by the load sensor and the data acquisition system. The formula for calculating the interface adhesion is:

[0103] σ = F / A

[0104] Among them, σ is the interfacial bonding force between recycled concrete aggregate and cement mortar, F is the tensile failure load measured by the load sensor, and A is the horizontal force area of ​​recycled concrete aggregate, which should be a 70mm×70mm cross section. The results are accurate to 0.01MPa. The interfacial bonding forces obtained from the various tests are shown in Table 2.

[0105] Table 2 Interface strength of mortar with different particle sizes of recycled aggregate

[0106]

[0107] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0108] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a recycled concrete aggregate specimen, characterized in that: Includes steps: Screen the recycled aggregates whose particle size deviation is less than or equal to the set particle size deviation as the aggregate to be tested; The aggregate to be tested is placed in the lower forming die, and the gap between the aggregates to be tested is controlled to be smaller than the set gap; Pour epoxy resin into the lower forming mold until the epoxy resin is filled to a set height, so as to obtain an epoxy resin layer formed under the aggregate to be tested after standing and hardening, and the set height is equal to half the height of the aggregate to be tested; Placing an upper molding die above the epoxy resin layer so that the upper molding die wraps the upper part of the aggregate to be tested, and the outer diameter of the upper molding die is smaller than the outer diameter of the lower molding die; Pour cement mortar into an upper forming mold and vibrate to form a cement mortar layer formed on the upper part of the aggregate to be tested after standing and solidifying; as well as Under standard test conditions, the recycled concrete aggregate specimens are cured to the set age.

2. The method for preparing recycled concrete aggregate specimens according to claim 1, characterized in that: In the step of screening recycled aggregates with a particle size deviation less than or equal to a set particle size deviation as aggregate to be tested, the set particle size deviation is 3 mm.

3. The method for preparing recycled concrete aggregate specimens according to claim 1, characterized in that: In the step of placing the aggregate to be tested in the lower forming mold and controlling the gap between the aggregates to be tested to be smaller than the set gap, the set gap is 2 mm.

4. The method for preparing recycled concrete aggregate specimens according to claim 1, characterized in that: In the step of screening recycled aggregates with a particle size deviation less than or equal to a set particle size deviation as the aggregate to be tested, the particle size of the recycled aggregate ranges from 5 mm to 31.5 mm, and the sphericity of the recycled aggregate is greater than or equal to 0.

9.

5. The method for preparing recycled concrete aggregate specimens according to any one of claims 1 to 4, characterized in that: In the recycled concrete aggregate specimen preparation method, the upper forming mold is made of Teflon material.

Citation Information

Patent Citations

  • Bond strength testing method of concrete rough aggregate interface

    CN101839831A